The Foggara: A Traditional System of Irrigation in Arid Regions - Boualem, Remini; Bachir, Achour; Rabah, Kechad (GeoScience Engineering, 2014)
This article discusses the traditional irrigation system in the oases of Touat, Gourara and Tidikelt. Since centuries, farmers use the system of foggaras for irrigation of palm groves and gardens. The results obtained following the inquiries and investigations carried out on the sites of foggaras, showed that since the eighties, drilling works multiplied in the oases of Touat, Gourara and Tidikelt. However, despite the application of these new techniques of water catchment, farmers still irrigate their gardens by traditional methods. For social, economic and environmental problems, foggaras degrade more and more; 50% of the foggaras decayed. Currently, the discharge of foggaras in service greatly diminished. The adoption of modern catchment techniques entails to the lowering of the water table.